Kemah Berkompeten: Mengasah Kemampuan Menyimak melalui Metode Bermain di Huta Silokidir - Sapri; Azahra, Bella; Khairani, Yesa Dwi; Rangkuti, Khairina Habib; Siagian, Amalia Alfina Br; Pane, Fizri Aspika Putri; Harahap, Azmi Oktari; Fadillah, Nurul; Sitompul, Buti Sarma (Jurnal Pengabdian Nasional (JPN) Indonesia, 2024)
This study investigates the participation of children in the "Competent Camp" program, which aims to enhance their listening skills through play activities within the Silokidir Forest. A qualitative methodology is employed, with an emphasis on case studies conducted across various educational institutions. Data were collected using participatory qualitative methods, with participants actively engaging in play activities designed to improve their listening skills. The findings indicate that interactive and dynamic play activities contribute to enhanced listening abilities among participants. For instance, participants demonstrated improved listening skills, evidenced by faster and more accurate responses during simulated tasks. This study underscores the effectiveness of outdoor experiences as a tool for skill enhancement, particularly in improving listening abilities among diverse student groups.